The Mixed Blessing in Subsidized Internet Access - Rob Frieden (International Telecommunications Society (ITS), 2017)
This article offers an unsponsored examination of current disputes whether national regulatory authorities (“NRAs”) should permit broadband carriers and content providers, such as Facebook, to subsidize broadband access to a limited, “walled garden” of content. The subsidy makes it possible for sponsored data access without debiting a monthly data allowance. Wireless subscribers, with service caps typically set at 1-5 Gigabytes allowed per month, can quickly exhaust their monthly allotment when streaming video content. Even so-called unlimited data plans in developed countries have monthly data thresholds that, if reached, trigger slower content delivery speeds and possibly degraded screen resolution of delivered video content. The article concludes that even though carriers and content providers serve profit maximizing goals in zero rating arrangements, the practice can have positive spillover effects including more access by impoverished users, stimulated interest in diversifying uses of wireless handsets and possible migration to broadband access options that equally support content consumption and creation. While carriers and content providers can migrate tentative, subsidized users into paying ones, zero rating also provides first time access opportunities, particularly for individuals least able to afford even extremely low cost access options available in many lesser developed countries. Additionally, zero rating can stimulate interest by consumers financially able to afford unsubsidized access, but heretofore uninterested in, or uninformed about the benefits. The article identifies ways for carriers and NRAs to limit subsidies in ways that accrue social benefits without creating an unlimited “free rider” opportunity for all wireless subscribers, regardless of ability to pay for service. The article suggests that carriers should offer zero rating opportunities on a conditional and promotional basis thereby making it more difficult for existing subscribers simply to use zero rating access as a way to avoid paying surcharges for exceeding data caps. While NRAs should not micro-manage carriers' service pricing, establishing qualification rules for access to zero rating fits with other universal service initiatives that rely on well calibrated and targeted subsidies to simulate broadband service demand and supply.
Keywords: 330